Teori Simulakrum Jean Baudrillard dan Upaya Pustakawan Mengidentifikasi Informasi Realitas - Azwar, Muhammad (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2014)
Librarians should have high sencitive to information overloaded. Deep understanding on Simulacrum Jean Baudrillardâs theory is needed to all. The ability to identify various of real and unreal information should be encouraged to librarians, as the result the end-users can access the needed information, not Simulacrum information. Some activities were taken by librarians in order to anticipate Simulacrum information, for instance, the way how they select any materials that being collected by the library, selecting digital content on its institution repository, literacy information program, dissemination information, etc.